Evaluation of artificial drug incorporation into hair for the production of quality control samples - Flavia Lopes Roveri; Ana Miguel Fonseca Pego; Sarah Eller; Tiago Franco de Oliveira; Mauricio Yonamine (Drug Analytical Research, 2021)
Hair analysis is thoroughly used in forensic toxicology although there are still some points of concern such as lack of reference material, whether for internal quality controls (IQC) or even for analytical validation process verification. Nonetheless spiked samples are still widely used, mainly for method development, it is not possible to evaluate its actual reproducibility and accuracy. As an alternative, IQC could be produced artificially by the laboratories themselves. The aim of this work was the evaluation of the phenomenon of artificial incorporation of drugs into hair to produce internal quality controls. These controls have been prepared according to the recommendations from the National Institute of Standards and Technology. For the amphetamine group, amphetamine and MDMA, showed different incorporation rates, of 0.17 up to 0.5% for amphetamine and 0.10 up to 0.4% for MDMA. As for cocaine, the incorporation rate was progressive over the course of days, ranging from 0.15 to 0.75%. The highest incorporation was found for diazepam, from 0.57%. to 3.75%. Lower rates were obtained for morphine, ranging from 0.08 to 0.25%, given that the incorporation rate of 0.25% has been reached on the ninth day. Some factors such as incubation time, agitation process and sample washing probably influenced the way analytes incorporate into the matrix including the effects of homogenization of the samples. Overall, knowing the incorporation profile of each analyte it is possible to produce IQC, with different concentrations. Thus, laboratories will have the fortified samples as a better tool for evaluating their own methodology.